Comparative Study of Natural and Synthetic Superdisintegrants in Orodispersible Metformin Tablet - Sachan, Anupam Kumar (Asian Journal of Pharmaceutical Research and Development, 2019)
Objective: The main objective of this study is comparative study of natural and synthetic superdisintegrants in orodispersible Metformin tablet by using direct compression method and wet granulation method. Method: Orodispersible Metformin tablet were prepared by wet granulation method and direct compression method by using different synthetic and natural superdisintegrants. Orodispersible tablets (ODTs) have received more interest in the pharmaceutical industry for their easy to use and self medication. ODTs overcome the problem of dysphagia (difficulty in swallowing) in the all group age of patients and advantage particularly for the paediatric and geriatric patients. Metformin hydrochloride (Hcl) is an orally administered antihyperglycemic agent, used in the management of non-insulin dependent (type-2) diabetes mellitus. Metformin orodispersible tablet is prepared by using two methods i.e. direct compression method and wet granulation method. Both methods are applied to prepare Orodispersible Metformin tablet. Orodispersible tablet of Metformin was prepared by using superdisintegrants from both natural and synthetic origin. In natural superdisintegrants we used the mucilage of Fenugreek and Lepidium sativum. In synthetic superdisintegrants we used crospovidone and sodium starch glycolate. Conclusion: In direct compression and wet granulation method final blend and granules were evaluated the flow properties like bulk density, tapped density, compressibility index, hausner’s ratio and angle of repose. The values of precompression parameter evaluated were found to be within the prescribed limit and indicated good flow properties. The data obtained from the post compression methods was studied. Other parameters such as wetting time, water absorption ratio were also evaluated. The formulation (F5) containing 10% crospovidone prepared by wet granulation method was found the optimize formulation. Keywords: Metformin Hcl, Orodispersible tablets, Superdisintegrants, Direct Compression, and Wet granulation Objective: The main objective of this study is comparative study of natural and synthetic superdisintegrants in orodispersible Metformin tablet by using direct compression method and wet granulation method. Method: Orodispersible Metformin tablet were prepared by wet granulation method and direct compression method by using different synthetic and natural superdisintegrants. Orodispersible tablets (ODTs) have received more interest in the pharmaceutical industry for their easy to use and self medication. ODTs overcome the problem of dysphagia (difficulty in swallowing) in the all group age of patients and advantage particularly for the paediatric and geriatric patients. Metformin hydrochloride (Hcl) is an orally administered antihyperglycemic agent, used in the management of non-insulin dependent (type-2) diabetes mellitus. Metformin orodispersible tablet is prepared by using two methods i.e. direct compression method and wet granulation method. Both methods are applied to prepare Orodispersible Metformin tablet. Orodispersible tablet of Metformin was prepared by using superdisintegrants from both natural and synthetic origin. In natural superdisintegrants we used the mucilage of Fenugreek and Lepidium sativum. In synthetic superdisintegrants we used crospovidone and sodium starch glycolate. Conclusion: In direct compression and wet granulation method final blend and granules were evaluated the flow properties like bulk density, tapped density, compressibility index, hausner’s ratio and angle of repose. The values of precompression parameter evaluated were found to be within the prescribed limit and indicated good flow properties. The data obtained from the post compression methods was studied. Other parameters such as wetting time, water absorption ratio were also evaluated. The formulation (F5) containing 10% crospovidone prepared by wet granulation method was found the optimize formulation. Keywords: